Characterization of TiO2 Nanofilms Obtained by Sol-gel and Anodic Oxidation - María Laura Vera; Miguel Ángel Alterach; Mario Roberto Rosenberger; Diego Germán Lamas; Carlos Enrique Schvezov; Alicia Esther Ares (Nanomaterials and Nanotechnology)
The influence of sol-gel dip-coating and anodic oxidation process parameters in producing thin TiO2 films is studied. As the size of the films is in the order of nanometres (20-140 nm), to obtain a precise measurement of their thickness and analyse their crystalline structures, glancing incidence angle X-ray techniques (X-ray reflectometry and Xray diffraction) using synchrotron radiation are used. A relationship between the colour and thickness of the films was found. This enables the film thickness to be estimated by the film colour. Within the range of the parameters studied, both techniques produce thin films with smooth surfaces which at most reproduce the roughness of the polished substrate. Independently of the technique, thermally-treated films thicker than 30 nm presented different crystalline structures with anatase and rutile phases.